A theoretical analysis of roll-over-web coating of couple stress fluid. (January 2018) - Ali, Nasir; Atif, Hafiz Muhammad; Javed, Muhammad Asif; Sajid, Muhammad
This paper presents the roll-coating analysis of couple stress fluid under lubrication approximation theory. The governing differential equation developed under the approximation is solved to get exact expressions for velocity and pressure gradient. The engineering quantities of interest such as pressure, roll-separating (load-carrying) force, and power input function are computed numerically. How the couple stress fluid material parameter affects velocity, pressure, pressure gradient, load-carrying force, and power input is shown graphically. One observes that couple stress model predicts higher pressure in the nip region when compared to the Newtonian model. The load-carrying force and power input exceed their Newtonian values for strong couple stress effects. Moreover, the separation point moves left of its Newtonian value with increasing couple stress effects.